Same evidence, varying viewpoints: three questions illustrating important differences between United States and European cholesterol guideline recommendations (2020)
In 2018, the AHA/ACC Multisociety Guideline on the Management of Blood Cholesterol was released. Less than one year later, the 2019 ESC/ EAS Dyslipidemia Guideline was published. While both provide important recommendations for managing atherosclerotic cardiovascular disease (ASCVD) risk through lipid management, differences exist. Prior to the publication of both guidelines, important randomized clinical trial data emerged on non-statin lipid lowering therapy and ASCVD risk reduction. To illustrate important differences in guideline recommendations, we use this data to help answer three key questions: 1) Are ASCVD event rates similar in high-risk primary and stable secondary prevention?; 2) Does imaging evidence of subclinical atherosclerosis justify aggressive use of statin and non-statin therapy (if needed) to reduce LDL-C levels below 55 mg/dL as recommended in the European Guideline?; 3) Do LDL-C levels below 70 mg/dL achieve a large absolute risk reduction in secondary ASCVD prevention?. The US guideline prioritizes both the added efficacy and cost implications of non-statin therapy, which limits intensive therapy to individuals with the highest risk of ASCVD. The European approach broadens the eligibility criteria by incorporating goals of therapy in both primary and secondary prevention. The current cost and access constraints of healthcare worldwide, especially amidst a COVID-19 pandemic, makes the European recommendations more challenging to implement. By restricting non-statin therapy to a subgroup of high- and, in particular, very high-risk individuals, the US guideline provides primary and secondary ASCVD prevention recommendations that are more affordable and attainable. Ultimately, finding a common ground for both guidelines rests on our ability to design trials that assess costeffectiveness in addition to efficacy and safety.